Einfluss von Poren in Lötverbindungen bei LED-Anwendungen - Rauer, Miriam; Xu, Ping; Reinhardt, Andreas; Kaloudis, Michael; Franke, Jörg (Elektronische Baugruppen und Leiterplatten - EBL, 2016)
A high-quality joint between LED and substrate is mandatory to take advantage of the whole value creation potential of LEDs and to avoid premature failures. In the course of this investigations the influence of voids in solder joints on the thermal, electrical and thermo-mechanical reliability on the application of high power LEDs are determined. For this purpose test assemblies with high and low voiding levels were produced and characterized by use of conventional X-ray inspection and computer tomography. The benefit of the non-destructive three-dimensional analysis of voids by means of CT, is that the exact void position and its volume are well-known and cracks are detectable. As part of this article the results of the active power cycle test are presented. Additionally to the experimental investigations finite element simu-lations should be performed to study specific void positions and sizes in detail.
Keywords: Bordnetze; E|P; LED; Lötverbindung; Poren; Simulation; Zuverlässigkeit

Investigation of the Influence of Voids n the Reliability of Solder Joints by Finite Element Method - Schwarzer, Christian; Fuchs, Dennis; Rauer, Miriam; Xu, Ping; Krügelstein, Andreas; Franke, Jörg; Kaloudis, Michael (SMTA International Conference Proceedings, 2017)

Investigation of the Influence of Voids on the Reliability of LED Solder Joints by Computer Tomography and Forward Voltage Measurement - Schwarzer, Christian; Fuchs, Dennis; Rauer, Miriam; Lang, Kurt-Jürgen; Krügelstein, Andreas; Kaloudis, Michael; Franke, Jörg (EMPC 2017, 2017)

Simulation-aided Analysis of the Influence of Voids on the Reliability of Solder-joints for LED-Applications - Xu, Ping; Rauer, Miriam; Kaloudis, Michael; Franke, Jörg (6th Electronics System-Integration Technology Conference (ESTC), 2016)
High power LEDs have become increasingly important for industrial applications due to their long life-cycle and high energy saving potential. To achieve the maximum efficiency and lifetime, the quality and stability of the LED packages must be ensured. A critical factor is the reliability of the solder joints, especially with lead-free solder alloys because of the process-induced voids during the soldering process and consequent failure mechanisms during service. This contribution focuses on the influence of the voids on the reliability of solder joints for high-power LED applications. Concerning the long time scale for the reliability tests such as temperature shock tests (TST) or power cycling tests (PCT), finite-element-method had been considered to enable a simulation-aided analysis and to gain a better understanding of the fatigue behavior of the solder joint with different voids distributions. In the simulation, all the models are based on the real experiments with produced test assemblies with high and low voiding levels. The test assemblies were characterized before and after the reliability tests by using computer tomography (CT) in order to document the crack initiation. Based on the measured dimensions of the solder joints, 3D-models were built with different sizes and positions of voids. For the material behaviors, the Garofalo equation is implemented for calculating the creep strain and to detect the crack initiation. Various test conditions (for TST and PCT) have also been taken account of in order to reduce the deviation between reality and simulation. Finally, the simulated results of crack initiation are compared with the results of real experimental data. The Comparison shows good correlation between simulations and experimental tests with respect to failure modes such as the position of cracks. Potentials and challenges of using numerical methods are also discussed for further studies.
Keywords: Bordnetze; E|P; FEM; LEDs; reliability; solder paste; Voids